2008
DOI: 10.1182/blood-2007-08-106195
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin mediates hepcidin expression in hepatocytes through EPOR signaling and regulation of C/EBPα

Abstract: Hepcidin is the principal iron regulatory hormone, controlling the systemic absorption and remobilization of iron from intracellular stores. Recent in vivo studies have shown that hepcidin is down-regulated by erythropoiesis, anemia, and hypoxia, which meets the need of iron input for erythrocyte production. Erythropoietin (EPO) is the primary signal that triggers erythropoiesis in anemic and hypoxic conditions. Therefore, a direct involvement of EPO in hepcidin regulation can be hypothesized. We report here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
161
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 36 publications
7
161
2
5
Order By: Relevance
“…Under the normal condition, hepatic hepcidin expression is prominently induced by erythropoietic demand, iron burden and inflammatory stimuli [66][67][68], of which the BMP family members and the IL-6 family cytokines are the essential upstream regulators [68,69]. Recent studies suggest that BMP6, rather than other BMP family members, is the key endogenous regulator of hepatic hepcidin expression at least in mice [70], and BMP6 likely governs the basal expression of hepatic hepcidin [71].…”
Section: Discussionmentioning
confidence: 99%
“…Under the normal condition, hepatic hepcidin expression is prominently induced by erythropoietic demand, iron burden and inflammatory stimuli [66][67][68], of which the BMP family members and the IL-6 family cytokines are the essential upstream regulators [68,69]. Recent studies suggest that BMP6, rather than other BMP family members, is the key endogenous regulator of hepatic hepcidin expression at least in mice [70], and BMP6 likely governs the basal expression of hepatic hepcidin [71].…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPa and C/EBPb are both potent and weak activators, respectively, of human and mouse hepcidin promoters (45). Furthermore, it has also been recently proposed that in conditions of anemia or hypoxia, erythropoietin (EPO) could act directly to repress hepcidin in hepatocytes through EPO receptor-mediated regulation of the transcription factor C/EBPa (46). STAT has recently been identified as one of the most important regulators of hepcidin, being essential for hepcidin expression during inflammatory conditions (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors involved in erythropoiesis is EPO, synthesized by the kidney in hypoxic conditions and known to inhibit hepcidin expression. Pinto et al (46) have proposed that EPO mediates hepcidin expression in hepatocytes through EPO receptor-mediated regulation of the transcription factor C/EBPa, which is present in the promoters of sea bass hepcidins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicated that erythropoietin can directly combine with erythropoietin receptor on the cell surface, which would cause the intracellular signal transduction to suppress the expression and DNA binding activity of transcription factor C/EBPa and phospho-STAT3/5, thereby inhibiting the expression of hepcidin. 17 However, because of the short half-life of erythropoietin in serum, frequent injection of high doses of erythropoietin is needed, resulting in poor tolerance and expensive cost in patients.…”
Section: Discussionmentioning
confidence: 99%